Complement activation product C4d in oral and oropharyngeal squamous cell carcinoma. (7th September 2015) - Ajona, D; Pajares, MJ; Chiara, MD; Rodrigo, JP; Jantus‐Lewintre, E; Camps, C; Suarez, C; Bagán, JV; Montuenga, LM; Pio, R
<x xml:space="preserve">Abstract</x> Objective Complement C4d‐containing fragments have been proposed as diagnostic markers for lung cancer. The purpose of this study was to evaluate the presence of C4d in oropharyngeal (OPSCC) and oral (OSCC) squamous cell carcinomas. Subjects and Methods C4d staining was analyzed by immunohistochemistry in 244 OPSCC surgical specimens. C4d levels were quantified by ELISA in resting saliva samples from 48 patients with oral leukoplakia and 62 with OSCC. Plasma samples from 21 patients with leukoplakia and 30 with oral carcinoma were also studied. Results C4d staining in OPSCC specimens was associated with nodal invasion (P = 0.001), histopathologic grade (P = 0.014), disease stage (P = 0.040), and focal‐adhesion kinase expression (P < 0.001). No association was found between C4d and prognosis. Saliva C4d levels were higher in patients with oral cancer than in subjects with leukoplakia (0.07 ± 0.07 vs 0.04 ± 0.03 μg ml−1, P = 0.003). The area under the ROC curve was 0.63 (95%CI: 0.55–0.71). Salivary C4d levels in stage IV patients were higher than in patients with earlier stages (P = 0.028) and correlated with tumor size (P = 0.045). Plasma C4d levels also correlated with salivary C4d levels (P = 0.041), but differences between patients with oral cancer and subjects with leukoplakia were not significant (1.26 ± 0.59 vs 1.09 ± 0.39 μg ml−1, P = 0.232). Conclusion C4d‐containing fragments are detected in oral primary tumors and are increased in saliva from patients with OSCC.